Impact of baseline feature tracking multi-detector row computed tomography-derived left ventricular global longitudinal strain on left ventricular functional recovery in TAVI patients. (25th November 2020) - Gegenava, T; Bijl, P; Vollema, M; Kley, F; Weger, A; Hautemann, D; Reiber, J; Ajmone-Marsan, N; Bax, J; Delgado, V
Abstract: Background: Advances in left ventricular (LV) analysis with dynamic multi-detector row computed tomography (MDCT) permit measurement of LV global longitudinal strain (GLS) and have shown their impact on risk stratification of patients with aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI). Purpose: To evaluate the influence of baseline feature tracking (FT) MDCT- derived LV GLS on LV functional recovery in severe AS patients undergoing TAVI. Methods: A total of 194 patients with severe AS (50% male, 80±7 years) with dynamic MDCT data allowing LV GLS measurement with a novel FT algorithm and having complete echocardiography evaluation at baseline, at 3–6 months and at 1 year follow-up were evaluated. FT MDCT-derived LV GLS was measured at baseline and the study population was divided according to a cut-off value of MDCT LV GLS −14% (≤−14% [more preserved LV systolic function] vs. >−14% [more impaired LV systolic function]). Results: Transthoracic echocardiography (TTE)-derived Left ventricular ejection fraction (LVEF) increased over time in both groups: in patients with preserved and reduced MDCT LV GLS, and reached a higher value in patients with preserved MDCT LV GLS (52±7% at baseline, 55±7% at 3–6 months, 58±7% at 1 year follow-up vs. 43±10% at baseline, 49±10% at 3–6 months, 53±11% at 1 year follow-up; p=0.016) (Figure 1). TTE-derived LV GLS also showed greater improvement for patients with preserved MDCT LV GLS (−17±3% at baseline, −18±3% at 3–6 months, −20±3% at 1 year follow-up vs. −12±3% at baseline, −15±3% at 3–6 months, −16±3% at 1 year follow-up; p=0.027) (Figure 1). Conclusions: In severe AS patients treated with TAVI, LV function improves significantly at 3–6 and at 12 months' follow-up and shows superior recovery in patients with more preserved baseline MDCT LV GLS, suggesting that MDCT-derived LV GLS has an important impact on LV functional recovery after TAVI. Funding Acknowledgement: Type of funding source: None